Targeted Synergy between Adjacent Co Atoms on Graphene Oxide as an Efficient New Electrocatalyst for Li–CO2 Batteries. (30th September 2019) - Zhang, Bin‐Wei; Jiao, Yan; Chao, Dong‐Liang; Ye, Chao; Wang, Yun‐Xiao; Davey, Kenneth; Liu, Hua‐Kun; Dou, Shi‐Xue; Qiao, Shi‐Zhang
Abstract: Li–CO2 batteries are an attractive technology for converting CO2 into energy. However, the decomposition of insulating Li2 CO3 on the cathode during discharge is a barrier to practical application. Here, it is demonstrated that a high loading of single Co atoms (≈5.3%) anchored on graphene oxide (adjacent Co/GO) acts as an efficient and durable electrocatalyst for Li–CO2 batteries. This targeted dispersion of atomic Co provides catalytically adjacent active sites to decompose Li2 CO3 . The adjacent Co/GO exhibits a highly significant sustained discharge capacity of 17 358 mA h g −1 at 100 mA g −1 for >100 cycles. Density functional theory simulations confirm that the adjacent Co electrocatalyst possesses the best performance toward the decomposition of Li2 CO3 and maintains metallic‐like nature after the adsorption of Li2 CO3 . Abstract : Targeted synergy between adjacent Co atoms on graphene oxide is an efficient new electrocatalyst for Li–CO2 batteries. Due to a targeted high mass‐loading, neighboring single Co atoms generate a synergetic interaction and provide continuous catalytic active sites for electrocatalysis of decomposition of Li2 CO3 with excellent capacity and cycling stability toward Li–CO2 batteries.